Clinical Development and Initial Approval of Novel Immune Checkpoint Inhibitors in Oncology: Insights From a Global Regulatory Perspective. Issue 3 (12th September 2018) - Serrano, Philippe; Hartmann, Markus; Schmitt, Elmar; Franco, Pedro; Amexis, Georgios; Gross, Jan; Mayer‐Nicolai, Christine
Abstract : Immune checkpoint inhibitors (ICI) have demonstrated meaningful patterns of clinical efficacy across various cancers. During their development, novel regulatory strategies and clinical design approaches were explored. This metrics‐based narrative review examines submission strategies and clinical evidence expectations of the US, European, and Japanese drug agencies, as well as their impact on approval and overall development times. Also discussed is the role of emerging clinical science and biomarker evaluation to get the first six ICI initially approved.